The EPPO/OLAF compendium of national procedures: Denmark - Hauck, Pierre; Schneider, Jan-Martin; Karakocaoğlu, Nur Sena; Meyer, Sophie; Laird, Alastair Alexander; Justus Liebig University Giessen (My University, 2025)
This Danish EPPO/OLAF volume explores Denmark’s crucial role in the fight against EU fraud. It discusses Danish rules on criminal investigations and procedure as well as mutual legal assistance in criminal matters. Analysing the Danish Administration of Justice Act 2022 the publication focuses on the newly introduced section 107a, which addresses the issue that Denmark and Ireland have withdrawn from the European Public Prosecutor's Office (EPPO). It presents the most recent working agreement between the EPPO and the Danish Ministry of Justice (of 31 August 2023). It also examines the impact of OLAF investigations on Danish justice by analysing the role of the national authorities involved in the PIF investigations and their laws.
Keywords: ddc:340; ddc:320